Probability and amount of medicines expenditure according to health insurance status in Kenya: A household survey in eight counties. (21st October 2021) - Wirtz, Veronika J.; Servan‐Mori, Edson; Mungai, John; Mboya, John; Rockers, Peter C.; Onyango, Monica A.; Kiragu, Zana Wangari; Laing, Richard
Abstract: Background: National and county governments in Kenya have introduced various health insurance schemes to protect households against financial hardship as a result of large health expenditure. This study examines the relationship between health insurance and medicine expenditure in eight counties in Kenya. Methods: A cross‐sectional study of collected primary data via household survey in eight counties was performed. Three measures of medicine expenditure were analysed: the probability of any out‐of‐pocket expenditure (OOPE) on medicines in the last 4 weeks; amount of OOPE on medicines; and OOPE on medicines as a proportion of total OOPE on health. Results: Out of the 452 individuals, those with health insurance ( n = 225) were significantly different from individuals without health insurance ( n = 227): overall, they were older, had a higher level of educational attainment and possessed more assets. Adjusting for covariates, individuals with health insurance had a reduced probability of OOPE on medicines (0.40, CI95% 0.197–0.827) and spent proportionally less on medicines out of total health expenditure (0.50, CI95% 0.301–0.926). Conclusions: Kenya has made great strides to scale up Universal Health Coverage including access to medicines. Prioritising enrollment of low‐income individuals with non‐communicable diseases can accelerate access to medicines and financial protection.